2017
DOI: 10.15408/ess.v7i2.4797
|View full text |Cite
|
Sign up to set email alerts
|

Prediksi Financial Distress Pada Perusahaan Manufaktur Di Bursa Efek Indonesia

Abstract: This study aims to identify, analyze, demonstrate and test the differences in health status between the model results Grover, Springate, and Zmijewski. The model used by investors who will invest in the company. This study has a characteristic that is tested three models and find the one best model. Data was tested using chi-square test. Results showed Hypothesis 1 accepted that there are differences in health status in the test model of Grover, Springate, and Zmijewski on manufacturing companies listed on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
17

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 1 publication
0
7
0
17
Order By: Relevance
“…Winaya et al (2020) who showed the results that each model has different predictions mentioned that it happened because the ratios used as variables in the analysis were different between each prediction model. Permana et al (2017) said that the prediction results of each model were different because each prediction model had different components or variables. H3: Zmijewski's model was the most accurate in predicting the bankruptcy of Indonesian retail companies.…”
Section: Discussionmentioning
confidence: 99%
“…Winaya et al (2020) who showed the results that each model has different predictions mentioned that it happened because the ratios used as variables in the analysis were different between each prediction model. Permana et al (2017) said that the prediction results of each model were different because each prediction model had different components or variables. H3: Zmijewski's model was the most accurate in predicting the bankruptcy of Indonesian retail companies.…”
Section: Discussionmentioning
confidence: 99%
“…0 Metode Grover merupakan model yang diciptakan Jeffrey S. Grover dengan melakukan perdesainan dan penilaian ulang terhadap model Altman Z-score. Setelah melakukan stepwise analysis, Grover menghasilkan persamaan sebagai berikut (Permana, 2017): G = 1,650X1 + 3,404X3 + 0,016ROA + 0,057 Variabel Independen 1) Kompensasi Manajerial Pengukuran variabel kompensasi manajerial diproksikan menggunakan kompensasi yang diberikan oleh perusahaan kepada dewan direksi dengan jumlah dari gaji, insentif, tunjangan remunerasi, THR, dan bonus atau tantiem yang diformulasikan sebagai berikut:…”
Section: Variabel Dependenunclassified
“…Hidayat [19]. Permana et al [22]. Financial Distress Prediction in Manufacturing Companies on the Indonesia Stock Exchange There is differences in health status in testing the Grover, Springate, and Zmijewski models.…”
Section: Past Researchmentioning
confidence: 99%